Nonemptiness and Compactness of Solutions Set for Nondifferentiable Multiobjective Optimization Problems - Xin-kun Wu; Jia-wei Chen; Yun-zhi Zou (Journal of Applied Mathematics)
A nondifferentiable multiobjective optimization problem with nonempty set constraints is considered, and the equivalence of weakly efficient solutions, the critical points for the nondifferentiable multiobjective optimization problems, and solutions for vector variational-like inequalities is established under some suitable conditions. Nonemptiness and compactness of the solutions set for the nondifferentiable multiobjective optimization problems are proved by using the FKKM theorem and a fixed-point theorem.